QUANTUM COMPUTING: UNVEILING OPPORTUNITIES, CHALLENGES, AND ETHICAL CONSIDERATIONS IN TECHNOLOGY AND BUSINESS - Safoev, Nuriddin; Djurayev , Musurmon Avlakulovich; Tuyboyov , Oybek Valijonovich (Innovative Development in Educational Activities, 2023)
This paper offers a comprehensive exploration of quantum computing, a transformative force poised to reshape technology and business landscapes. Beginning with an exploration of its foundational principles, the paper delves into the far-reaching implications of quantum algorithms, particularly their impact on existing cryptographic measures. Simultaneously, it uncovers significant opportunities in key sectors such as finance, healthcare, and logistics. The narrative progresses to examine the emergence of novel business models, exemplified by Quantum-as-a-Service (QaaS) and augmented AI capabilities. While highlighting the myriad possibilities, the paper also addresses the challenges and ethical considerations accompanying the rapid ascent of quantum technologies. Stressing the need for collaborative efforts among businesses, policymakers, and technologists, the article advocates for a balanced and responsible approach to quantum adoption.